Comparison of Nasal and Oropharyngeal Bleeding in Video Laryngoscopy Versus Direct Laryngoscopy for Nasotracheal Intubation in Maxillofacial Trauma: A Randomized Controlled Trial - Ayman Mohamady Eldemrdash; Mohamed A. Alazhary; Zaher Zaki Zaher; Tarek S. Hemaida; Mohammed Essam Yahia; Soudy S. Hammad (Anesthesiology Research and Practice, 2025)
Trial Registration: ClinicalTrials.gov identifier: NCT06386757